2007
DOI: 10.1161/atvbaha.106.136382
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evidence for a Role of Adipose Tissue SR-BI in the Nutritional and Hormonal Regulation of Adiposity and Cholesterol Homeostasis

Abstract: Objectives-This study examines the role of insulin and angiotensin II in high-density lipoprotein (HDL) metabolism by focusing on the regulation and function of scavenger receptor type-BI (SR-BI) in adipose tissue. Methods and Results-Insulin or angiotensin II injection in wild-type mice induced a decrease in circulating HDL and it was associated with the translocation of SR-BI from intracellular sites to the plasma membrane of adipose tissue. Refeeding upregulated adipose HDL selective cholesteryl esters upta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 31 publications
(23 reference statements)
1
38
0
1
Order By: Relevance
“…A recent study demonstrated that injecting Ang II into wild-type mice reduced circulating highdensity lipoprotein (HDL), which was associated with the translocation of scavenger receptor type B1 (SR-B1) proteins to the plasma membrane in adipose tissue [28]. Similar results were obtained in transgenic mice overexpressing angiotensinogen in adipose tissue, raising the possibility that elevations in adipocyte-derived Ang II may contribute to dyslipidemias of obesity through regulation of adipocyte SR-BI and HDL clearance.…”
Section: Effects Of Ang II On Adipocytesmentioning
confidence: 83%
“…A recent study demonstrated that injecting Ang II into wild-type mice reduced circulating highdensity lipoprotein (HDL), which was associated with the translocation of scavenger receptor type B1 (SR-B1) proteins to the plasma membrane in adipose tissue [28]. Similar results were obtained in transgenic mice overexpressing angiotensinogen in adipose tissue, raising the possibility that elevations in adipocyte-derived Ang II may contribute to dyslipidemias of obesity through regulation of adipocyte SR-BI and HDL clearance.…”
Section: Effects Of Ang II On Adipocytesmentioning
confidence: 83%
“…However, adipose tissue is a major pool of free cholesterol (Krause and Hartman, 1984;Prattes et al, 2000) and some studies suggest an underappreciated role of adipose tissue in cholesterol metabolism (Verghese et al, 2007;Yvan-Charvet et al, 2007). Exposure of rats to clozapine and/or olanzapine increased the accumulation of cholesterol in liver (Ferno et al, 2009) and adipose tissue (Jassim et al, 2012).…”
Section: Antipsychotics Dyslipidemia and Cardiovascular Diseasementioning
confidence: 99%
“…Consistent with the view that adipose tissue behaves as a cholesterol sink, and its accumulation is proportional to triglycerides in response to nutritional changes to maintain cellular integrity and to regulate cellular hypertrophy, it is not surprising that adipocytes have developed a unique ability to deal with cholesterol (1). It may be for this reason that adipocytes have evolved with an extremely limited capacity to perform de novo cholesterol synthesis (1) but possess multiple strategies to extract cholesterol from circulating lipoproteins (5,6). Despite cholesterol being delivered as cholesteryl ester in adipocytes, approximately 95% of cholesterol paradoxically exists as free cholesterol (FC) (7) and resides in the plasma membrane or the cytosolic interface of lipid droplets where it is readily available for mobilization (8).…”
mentioning
confidence: 99%
“…This contrasts to scavenger receptor class B type I (SR-BI), which is not an LXR target and facilitates the bidirectional flux of cholesterol depending on the cholesterol status of the cells (11). Remarkably, HDL cholesterol transport machinery is highly represented in adipocytes (5,6,13) but the relevance to obesity and metabolic complications remains poorly understood. While LXR-deficient mice are leaner than littermate controls and are protected against diet-induced obesity, the mechanisms that control fat loss in these mice are still a matter of debate and could involve either reduced lipogenesis, enhanced lipid oxidation and lipolysis, or reduced cholesterol efflux pathways (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation